Areas of endemism and conservation status of Galianthe species (Spermacoceae, Rubiaceae) in the Neotropics. Issue 1 (31st December 2022) - Florentín, Javier Elías; Salas, Roberto Manuel; Jarvie, Scott; Svenning, Jens-Christian; Gomez, Juan Manuel Díaz
Abstract : Areas of endemism are a standard unit of biogeography and are commonly used for analytical biogeographic analyses as a criterion to identify areas for conservation. Galianthe is a genus of 56 species of mainly herbaceous plants from the family Rubiaceae found in the Neotropics, occurring in campos rupestres (quartzitic rock outcrops), cerrado (savanna), lowland grasslands, campos de altitude (highland grasslands), sasonally dry tropical forests ( caatinga vegetation ), and savanna hillsides. Currently, the conservation status assessment is only known for eleven species of Galianthe, and there have been no previous attempts to identify areas of endemism for the genus. In view of this, we used the NDM/VNDM software to analyze the distribution of the 56 species of Galianthe to identify areas of endemism and to recognize which species define each area. We also evaluated the conservation status of forty-five species for first time, according to the International Union for Conservation of Nature (IUCN) guidelines. Our finding identified 12 areas of endemism with three cell sizes, mainly in the eastern part of Paraguay and southern Brazil. Illustrating the general biodiversity crisis, 41% of the Galianthe species (23 spp.), were evaluated as Endangered due to their degree of endemism and destruction of their habitat, while 31 species were evaluated as not threatened and two species had Insufficient Data. In turn, only five threatened species were found within or on the periphery of protected areas. We consider that although protected areas are designed to protect biodiversity, in recent decades they have experienced different degrees of threat. Due to the high risk of many species of the genus, it is necessary to consider restoration (as a complement to conservation) of the processes that maintain grasslands to conserve unique, endemic and threatened species.